2019
DOI: 10.1177/1460458219891377
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing smartphone intervention features to improve chronic disease management: A rapid review

Abstract: While there are an increasing number of mobile health applications to facilitate self-management in patients with chronic disease, little is known about which application features are responsible for impact. The objective was to uncover application features associated with increased usability or improved patient outcomes. A rapid review was conducted in MEDLINE for recent studies on smartphone applications. Eligible studies examined applications for adult chronic disease populations, with self-management conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Moreover, only some include interactive components, such as support for self-care and communication with health care professionals and peers for immediate clinical management [ 7 , 9 - 12 ]. A key aspect of digital interventions is to understand how they operate and how they can be enhanced by assessment of usage and user experiences [ 13 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only some include interactive components, such as support for self-care and communication with health care professionals and peers for immediate clinical management [ 7 , 9 - 12 ]. A key aspect of digital interventions is to understand how they operate and how they can be enhanced by assessment of usage and user experiences [ 13 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only some include interactive components, such as support for self-care and communication with health care professionals and peers for immediate clinical management [7,[9][10][11][12]. A key aspect of digital interventions is to understand how they operate and how they can be enhanced by assessment of usage and user experiences [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for exclusion included content tailored to a specific disease, protocols or design studies, study registrations, and additional reasons can be found in Figure 1. No further studies were found after back-referencing reviews in digital behaviour change interventions [27,11,13,28,15,24,12].…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Digital health technologies are enabling real-time customisation of care by providing means for monitoring, anticipating, responding, and learning from patients' reported data and vital signs measured [10]. Digital technologies such as internet of things (IoTs) and mobile health systems (mHealth) have been used to exchange real-time data through multiple devices to assess disease progression, intervention effective-ness, acceptability, and other patient's specific parameters [11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%